Mesophilic, thermophilic and hyperthermophilic acidogenic fermentation of food waste in batch: Effect of inoculum source. (15th March 2019) - Arras, W.; Hussain, A.; Hausler, R.; Guiot, S.R.
Graphical abstract: Highlights: No impact of different inoculums and operating temperature on the hydrolysis efficiency. Hyperthermophilic conditions increased hydrolysis rate during start-up. Highest fermentation yield obtained at thermophilic conditions. Mesophilic conditions resulted in highest VFA yield. Lactic fermentation favored at 70 °C, regardless the inoculum source. Abstract: Distinctions in hydrolysis and acidogenesis were examined for a series of anaerobic batch reactors inoculated with three different anaerobic mixed cultures (mesophilic, thermophilic and hyperthermophilic anaerobic sludge) and operated at the temperature of inoculum's origin and additionally at 70 °C. Hyperthermophilic temperatures led to increased hydrolysis rates during the start-up stage but a rapid drop in pH limited the overall hydrolysis efficiency, indicating the importance of pH control to sustain the high reaction rates at higher temperatures. No significant difference ( P  >  0.05 ) was observed among hydrolysis efficiencies obtained for different reactors which ranged between 27 ± 3% and 40 ± 14%. The highest fermentation yield of 0.44 g COD of fermentation products/g VSS-CODadded was obtained under thermophilic conditions, followed by mesophilic (0.33 g COD ferm. prod./g VSS-CODadded ) and hyperthermophilic conditions (0.05–0.08 g COD ferm. prod./g VSS-CODadded ). Fermentative performance was better at mesophilic and thermophilic conditions as indicated by improved production of volatile fatty acids (VFA). VFAs accounted for 60–71% of the solubilised matter at thermophilic and mesophilic conditions. Acetic acid formed the primary VFA (70%) at mesophilic temperatures, while butyric acid was the major VFA at thermophilic (60%) conditions. Hyperthermophilic conditions led to increased production of lactic acid, which comprised up to 32% of the solubilised matter. Overall, the results indicate that different operating temperatures may not significantly affect the substrate degradation efficiency but clearly influence the biotransformation pathways.